PENGARUH BENTUK DAN LETAK CELAH PELOLOSAN (Escape Gap) PADA ALAT TANGKAP PENGILAR TERHADAP KELESTARIANSUMBERDAYA IKAN - Hadiah Witarani Puspa; T. Ersti Yulika Sari; Irwandy Syofyan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted during of March until June 2016 in Kampar River and Laboratory of Fishing Gear and Material Faculty of Fisheries and Marine Science University of Riau. It aim to determine effectiveness of shapes and potitions of escape gap. The method used are survey and experiment method and then use Analysist of Variance to complete the experiment. The results of the analysis show that the escape gap which square shape on center was effective because the value of effectiveness has 0.9%.Keywords : Pengilar, Escape Gap, Kampar